Cell dedifferentiation and multiplication of Burdock (Arctium Lappa) as a medicinal plant - Zebarjadi, Alireza; Kazem, Samaneh; Kahrizi, Danial (Cellular and Molecular Biology, 2018)
Arctium lappa L. (Burdock) is an important plant with various pharmacological effects. According to the importance of this plant, optimization of its tissue culture will lead to more investigation and application of it. The aim of this study was to develop protocols for callus induction and shoot regeneration of A. lappa. In order to optimize of tissue culture in A. lappa, callus induction, indirect regeneration and direct regeneration were carried out in factorial experiment based on Completely Randomized Designs (CRDs). Hypocotyl and cotyledon were cultured on the Murashige and Skoog (MS) medium supplemented with different concentrations and combinations of 2,4-Dichlorophenoxyacetic acid (2,4-D) and 6-Benzylaminopurine (BAP) for callus induction. In indirect regeneration experiment various levels of BAP and Î±-Naphthaleneacetic acid (NAA) and two types of explants (calli derived from cotyledon and hypocotyl) were investigated. In direct regeneration section, various levels of BAP plus 2 mg/l NAA and different explants (cotyledon, hypocotyl and bud) were compared. In both cotyledon and hypocotyl, the maximum callus induction was observed on a media containing 2 mg/l 2,4-D plus 1 mg/l BAP (100% and 76.19% respectively). The highest percentage of indirect regeneration (65%) was observed at 1 mg/l BAP plus 0.5 mg/l NAA on calli from hypocotyl. The highest percentage of direct regeneration (90.33) was observed in hypocotyl with a lateral bud explant on MS medium supplemented with 0.5 mg/l BAP plus 2 mg/l NAA. In this study, optimization of tissue culture protocol for A. lappa was carried out as a research technique, as well as technique for further exploitation of this plant.